Organic chemistry - Hart, Harold
Contains solutions to both in-text and end-of-chapter problems with an explanation of the answers. For each chapter, the guide provides a summary, learning objectives, and a summary of synthetic methods and reaction mechanisms. Review problems on synthesis and 100 multiple-choice questions offer students additional problem-solving practice